2016
DOI: 10.1097/meg.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in childhood: etiology, clinical features, and prognosis

Abstract: Our findings show that unknown causes are still prevalent in stone formation and that ursodeoxycholic acid exerts no effect on stone dissolution; however, diagnosis at younger than 2 years of age, a single stone, and small size of stone are factors affecting dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…Previous studies regarding the prevalence of GS have reported a bimodal distribution with a small peak in infancy that increases throughout adolescence showing a marked female preponderance [ 5 11 12 ]. Boys and girls are equally affected during early childhood; however, a clear female preponderance observed during adolescence is similar to that observed in adulthood [ 3 5 11 13 ]. Mehta et al [ 5 ] reported an increase in the mean age of diagnosis of GS disease.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies regarding the prevalence of GS have reported a bimodal distribution with a small peak in infancy that increases throughout adolescence showing a marked female preponderance [ 5 11 12 ]. Boys and girls are equally affected during early childhood; however, a clear female preponderance observed during adolescence is similar to that observed in adulthood [ 3 5 11 13 ]. Mehta et al [ 5 ] reported an increase in the mean age of diagnosis of GS disease.…”
Section: Discussionmentioning
confidence: 67%
“…UDKA tedavisinin safra kesesi taşı olan hastalarda, taşın çözünmesinde etkili olup olmadığı tartışmalı olsa da, semptomların hafifletilmesine yarar sağlayabileceği düşünülmektedir (22,23) . Çalışmamızda, Grup 2'de UDKA tedavisi alan hastalar ile semptomatik hastaların daha fazla olması bağlantılı olabilir.…”
Section: Discussionunclassified
“…The rate of patients who did not have risk factors ranges between 23.2% and 52.5% in the literature (7,8,16). In the current study, we did not identify any risk factors in 36.1% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for gallstones were searched regarding the studies of Gokce et al 7and Serdaroglu et al (8). Obesity, family history, ceftriaxone usage, staying in the intensive care unit, total parenteral nutrition (TPN) usage, diabetes, ileum resection, the presence of Down syndrome, and history of cardiac surgery were investigated as risk factors.…”
Section: Risk Factorsmentioning
confidence: 99%